How the OH reactivity affects the ozone production efficiency: case studies in Beijing and Heshan, China - Yang, Y. D.; Shao, M.; Kessel, S.; Y. Li; Lu, K. D.; Lu, S. H.; Williams, J.; Zhang, Y. H.; L.M. Zeng; Noelscher, A. C.; Y.S. Wu; XM Wang; et al. (Atmospheric Chemistry and PhysicsAtmospheric Chemistry and PhysicsAtmospheric Chemistry and Physics, 2017)
Total OH reactivity measurements were conducted on the Peking University campus (Beijing) in August 2013 and in Heshan (Guangdong province) from October to November 2014. The daily median OH reactivity was 20 +/- 11 s(-1) in Beijing and 31 +/- 20 s(-1) in Heshan, respectively. The data in Beijing showed a distinct diurnal pattern with the maxima over 27 s(-1) in the early morning and minima below 16 s(-1) in the afternoon. The diurnal pattern in Heshan was not as evident as in Beijing. Missing reactivity, defined as the difference between measured and calculated OH reactivity, was observed at both sites, with 21% missing reactivity in Beijing and 32% missing reactivity in Heshan. Unmeasured primary species, such as branched alkenes, could contribute to missing reactivity in Beijing, especially during morning rush hours. An observation-based model with the RACM2 (Regional Atmospheric Chemical Mechanism version 2) was used to understand the daytime missing reactivity in Beijing by adding unmeasured oxygenated volatile organic compounds and simulated intermediates of the degradation from primary volatile organic compounds (VOCs). However, the model could not find a convincing explanation for the missing reactivity in Heshan, where the ambient air was found to be more aged, and the missing reactivity was presumably attributed to oxidized species, such as unmeasured aldehydes, acids and dicarbonyls. The ozone production efficiency was 21% higher in Beijing and 30% higher in Heshan when the model was constrained by the measured reactivity, compared to the calculations with measured and modeled species included, indicating the importance of quantifying the OH reactivity for better understanding ozone chemistry.
Keywords: amazon rain-forest; atmospheric chemistry mechanism; comprehensive observations; isoprene oxidation; metropolitan-area; mexico-city; pearl river delta; probe technique; urban atmosphere; volatile organic-compounds